How do you simplify \frac { k - 2} { 3k + 3} - \frac { k + 1} { 3k + 3}?

2 Answers
Nov 26, 2017

(k-2)/(3k+3)-(k+1)/(3k+3)=-1/(k+1)

Explanation:

As in (k-2)/(3k+3) and (k+1)/(3k+3),

denominator is common,

while adding such fractions we can add / subtract numerators keeping denominators same to get result.

Hence (k-2)/(3k+3)-(k+1)/(3k+3)

= (k-2-(k+1))/(3k+3)

= (k-2-k-1)/(3k+3)

= (cancelk-2-cancelk-1)/(3k+3)

= -3/(3k+3)

= -(3xx1)/(3(k+1))

= -1/(k+1)

Nov 26, 2017

the simplified term is (-1)/(k+1)

Explanation:

the given equation is (k-2)/(3k+3)-(k+1)/(3k+3) since the LCM is same we can directly subtract the given 2 terms
we get,(k-2-k-1)/(3k+3)=(-3)/(3k+3)=-3/(3(k+1))=(-1)/(k+1)